Peningkatan Usaha Kecil Rumah Tangga Jemblem Frozen Berbahan Dasar Singkong di Kelurahan Kedungkendang, Malang: Increasing Small Household Businesses for Cassava Frozen Jemblem in Kedungkendang Village, Malang - Rani, Abdul; Kurniati, Rini Rahayu; Aini, Fitria Nugraha; Hidayat, Nandika Rahmat; Maula, Lia Rohmatul (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Kedung Kandang sub-district, Malang city, is one of the centers for small household businesses in the form of frozen jemblem, where this product is a traditional food made from cassava. However, these businesses still use traditional methods when processing it. This community service activity aims to help partner businesses thereby assisting in the form of jemblem processing machines and faster and more hygienic methods for making frozen jemblem. The method of this community service activity is by coordinating with partners for the process of making cassava grinding machines and providing technical guidance regarding methods of using cassava grinding machines. This activity resulted in the partners receiving assistance in the form of a cassava grinding machine which the partners could experience directly. Partners feel that having this cassava grinding machine can speed up the production process so that it can increase the sales turnover of frozen jemblem. Apart from that, with the cassava grinding machine, the frozen jemblem production process becomes more hygienic.